2018
DOI: 10.1016/j.jfda.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Designing a biochip following multiplex polymerase chain reaction for the detection of Salmonella serovars Typhimurium, Enteritidis, Infantis, Hadar, and Virchow in poultry products

Abstract: Salmonella-contaminated foods, especially poultry-derived foods (eggs, chicken meat), are the major source of salmonellosis. Not only in the European Union (EU), but also in the United States, Japan, and other countries, has salmonellosis been an issue of concern for food safety control agencies. In 2005, EU regulation 1003/2005 set a target for the control and reduction of five target Salmonella enterica serovars-S. Typhimurium, S. Enteritidis, S. Infantis, S. Hadar, and S. Virchow-in breeding flocks. Thus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…These analyses revealed that a sub-group of isolates, all confirmed by serotyping as S. Enteritidis and having either atypical or 9b phage types, were positive for the chromosomal sdfI marker but negative for the prot6e gene located on the S. Enteritidis virulence plasmid and which is believed to contribute to the ability of S. Enteritidis to survive in and be transmitted via eggs (Clavijo et al, 2006). Given that the prot6e gene is frequently used for S. Enteritidis detection (Malorny et al, 2007;Chiang et al, 2018) it was felt that further characterisation of these prot6enegative isolates was warranted. It was notable that all these prot6e-isolates originated from facilities identified as duckproducing facilities while all the prot6e+ isolates came from chicken or more general poultry-producing facilities.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses revealed that a sub-group of isolates, all confirmed by serotyping as S. Enteritidis and having either atypical or 9b phage types, were positive for the chromosomal sdfI marker but negative for the prot6e gene located on the S. Enteritidis virulence plasmid and which is believed to contribute to the ability of S. Enteritidis to survive in and be transmitted via eggs (Clavijo et al, 2006). Given that the prot6e gene is frequently used for S. Enteritidis detection (Malorny et al, 2007;Chiang et al, 2018) it was felt that further characterisation of these prot6enegative isolates was warranted. It was notable that all these prot6e-isolates originated from facilities identified as duckproducing facilities while all the prot6e+ isolates came from chicken or more general poultry-producing facilities.…”
Section: Introductionmentioning
confidence: 99%
“…A novel PCR was also developed for identification of Infantis based on flagellin fljB gene, 49 and Virchow-specific primers were designed for the detection of Virchow. 50 These results indicate that a set of MCDA assays targeting seven serovar/lineage-specific gene markers can rapidly detect and serotype the five most common and clinically relevant Salmonella serovars. Seven serovar/ lineage-specific gene markers, STM4494, SEN1384/ R561_RS18155, SESV_RS06060, SeSPB_A1749/SeS-PA_A1352, and L287_11788, 21 were used to develop Typhimurium, Enteritidis-clade B/Enteritidis-clade A/C, Virchow, Saintpaul-I/Saintpaul-II, and Infantis MCDA assays, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…(0.85, 1/117) was also observed in the group_27297 gene. In addition, Newp and Newspe genes were evaluated as PCR targets for Salmonella serovar Newport detection in a previous report and the results showed almost all of tested strains belonged to serovar Newport, Hadar, Bovismorbificans, Kottbus, Blockley, Manhattan, Litchfield, Glostrup, and several strains belonged to serovar Virchow and Muenchen were amplified by Newp gene; in order to distinguish serovar Newport and Hadar, the Newspe marker was designed, which showed 93.3% (28/30) strains for Newport and only S. Blockey were amplified Newspe gene (Chiang et al, 2018). This result was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we obtained seven novel single targets to detect Salmonella serovar Hadar and Albany. The HSR3 and Hadspe (hypothetical protein) genes were evaluated as PCR targets for Salmonella serovar Hadar detection and the results showed high specificity (100%) of this gene (Bugarel et al, 2017;Chiang et al, 2018). Compared to previous reports, the percentage of genomic sequences of strains for the four novel genes (group_20134, group_22774, group_29844, and group_29846) and HSR3 specific for serovar Hadar presence in target strains was higher (97.56%, 40/41) than in the Hadspe (82.93, 34/41), whereas in non-target serovars, the HSR3 genes were observed in serovars Paratyphi B and Tees (0.29%, 2/684).…”
Section: Discussionmentioning
confidence: 99%